2016
DOI: 10.1002/bem.22004
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellins are involved in effect of near‐null magnetic field on Arabidopsis flowering

Abstract: We previously found that flowering of Arabidopsis was suppressed by near-null magnetic field, which was related to the modification of cryptochrome. To disclose the physiological mechanism of this effect, we detected gibberellin (GA) levels and expressions of GA biosynthetic and signaling genes in wild type Arabidopsis plants and cryptochrome double mutant, cry1/cry2, grown in near-null magnetic field. We found that levels of GA , GA , GA , and GA in wild type plants in near-null magnetic field were significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…We then wanted to disclose the physiological mechanism of near-null magnetic field effect on Arabidopsis flowering. In our previous research, we found that GA was involved in the effect of near-null magnetic field on Arabidopsis flowering, and that GA level and GA biosynthetic genes in Arabidopsis were downregulated by near-null magnetic field [Xu et al, 2017]. In our present study, another important plant hormone, auxin, which also plays an important role in Arabidopsis flowering, was investigated to test whether auxin is also involved in the effect of near-null magnetic field on Arabidopsis flowering.…”
Section: Discussionmentioning
confidence: 82%
“…We then wanted to disclose the physiological mechanism of near-null magnetic field effect on Arabidopsis flowering. In our previous research, we found that GA was involved in the effect of near-null magnetic field on Arabidopsis flowering, and that GA level and GA biosynthetic genes in Arabidopsis were downregulated by near-null magnetic field [Xu et al, 2017]. In our present study, another important plant hormone, auxin, which also plays an important role in Arabidopsis flowering, was investigated to test whether auxin is also involved in the effect of near-null magnetic field on Arabidopsis flowering.…”
Section: Discussionmentioning
confidence: 82%
“…According to the data of the Table, closest to the primary physical level are studies that report on the involvement of gene expression in magnetoreception, e.g. [80, 108, 120, 123] and [139, 144, 156, 162, 166, 173], with different genes expressing in different situations. This suggests that the MF targets are rather physical and distributed, but they operate as magnetic receptors only in some specific conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In plants, recent reports revealed that variation of MF intensity affects photoreceptor activity (Agliassa et al, 2018b) and light-dependent processes such as leaf movement, stomatal conductance, and chlorophyll content (Galland and Pazur, 2005;Maffei, 2014). Furthermore, changes in the hormone levels, for instance, auxin and gibberellin, as well as a delay in flowering time have also been observed under near null MF (NNMF) conditions (Xu et al, 2012(Xu et al, , 2017(Xu et al, , 2018Agliassa et al, 2018a). Such delayed transition to flowering under NNMF is likely involved in the Angiosperms speciation during GMF reversals (Maffei, 2014;Occhipinti et al, 2014;Bertea et al, 2015), suggesting a possible contribution of the GMF magnitude on plant evolution.…”
Section: Introductionmentioning
confidence: 99%